PENGARUH SELF-REGULATED LEARNING DAN DUKUNGAN SOSIAL TERHADAP KEMATANGAN KARIER SISWA AKUTANSI KEUANGAN LEMBAGA DI SMK - Khoirunnisa Dini Rachmawati; Binti Muchsini (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2025)
The main focus of the research aims to determine the influence of self-regulated learning on career maturity, the influence of social support on career maturity, as well as self-regulated learning and career maturity. This research is a quantitative descriptive research with a correlational approach. The population of this research were 107 Class XII students majoring in Accounting and Finance at Vocational School Institutions in Karanganyar with a sample of 84 students. The sampling technique uses proportional stratified random sampling and data collection through distributing questionnaires and tests. Simple linear regression analysis and multiple linear regression analysis are data analysis techniques use in the research. The results of this research show that (1) there is an influence between self-regulated learning on career maturity; (2) there is an influence of social support on career maturity; and (3) there is self-regulated learning and social support for career maturity.Keywords: Career Maturity; Self-Regulated Learning; Social Support